Digitalisasi Kitab Nadham Batu Ngompal Karya TGKH. Muhammad Zainuddin Abdul Madjid Berbasis OPF Flipbook - Hariman Bahtiar; Aswian Editri Sutriandi; Muhammad Djamaluddin (Infotek: Jurnal Informatika dan Teknologi, 2020)
TGKH. Muhammad Zainuddin Abdul Madjid is one of the charismatic figures and scholars who came from Lombok Island. Many works have been produced by the purchase during his life, to be used as a guide for students and pilgrims who buy and lead. Maulana Shaykh's works still use conventional media in the form of paper. With this conventional media, mostly with frequent use or improper placement, it can make the media become damaged. The use of technology to preserve and preserve the works of charismatic figures and great scholars such as TGKH. Muhammad Zainuddin Abdul Madjid is very important. One of the works of purchase is Nazam Batu Ngompal, Nadham "Batu Ngompal" is one of the books that explain how to read the Qur'an fluently and in tartil. With the creation of the Nadham Batu Ngompal book in digital form, it helps students and worshipers to read your purchases from anywhere. One of the advantages of the Nadham Batu Ngompal e-book is that this e-book uses the OPF flipbook format so that when we open it as if we are opening the original book, and besides providing the text, this e-book also provides sound poetry reading facilities in the book. So besides reading, we can also listen to the sound of the poetry that is in the contents of the book at once.DOI : 10.29408/jit.v3i2.2288